Le miroir aux alouettes : destin sociologique des images du nu indigène - François Pouillon; Michel Mégnin (L’Année du Maghreb)
Postcards of the colonial era showing native women half naked have been used recently in a number of books which, somewhat paradoxically, condemn the fabrication and dissemination of the very images they display. The prefaces to these books, written by authors who are part of an intellectual diaspora, demonstrate the persistence of relations that Maghreb societies maintain with their women. We see reiterated the strong Mediterranean drive for endogamy that was studied in her time by Germaine Tillion, in Le Harem et les cousins (1966). Post-colonial arguments used in these texts thus appear as the “fig leaf” for more fundamental anthropological determinations.